2010
DOI: 10.1016/j.stem.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF Promotes the Proliferation of Developing Cardiomyocytes In Vivo and in Derivation from ESCs and iPSCs

Abstract: During a screen for humoral factors that promote cardiomyocyte differentiation from embryonic stem cells (ESCs), we found marked elevation of granulocyte colony-stimulating factor receptor (G-CSFR) mRNA in developing cardiomyocytes. We confirmed that both G-CSFR and G-CSF were specifically expressed in embryonic mouse heart at the midgestational stage, and expression levels were maintained throughout embryogenesis. Intrauterine G-CSF administration induced embryonic cardiomyocyte proliferation and caused hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 32 publications
4
73
0
Order By: Relevance
“…This finding is partially consistent with studies on mouse embryonic stem cells (mESCs) that demonstrate that the administration of Noggin before the initiation of differentiation promotes cardiogenesis [9]. Further comparing Noggin-treated cells with nontreated cells revealed that granulocyte colony-stimulating factor (G-CSF) promotes the proliferation of developing cardiomyocytes derived from mESCs [30]. Noggin sustains the undifferentiated proliferation of hESCs [31], and BMP4 is required for mESC self-renewal [32].…”
Section: Discussionsupporting
confidence: 83%
“…This finding is partially consistent with studies on mouse embryonic stem cells (mESCs) that demonstrate that the administration of Noggin before the initiation of differentiation promotes cardiogenesis [9]. Further comparing Noggin-treated cells with nontreated cells revealed that granulocyte colony-stimulating factor (G-CSF) promotes the proliferation of developing cardiomyocytes derived from mESCs [30]. Noggin sustains the undifferentiated proliferation of hESCs [31], and BMP4 is required for mESC self-renewal [32].…”
Section: Discussionsupporting
confidence: 83%
“…Such evidence indicated that asymmetric protein distribution produces asymmetric cell division, which has a critical role in maintaining the SC population. In our previous screen for myocyte differentiationpromoting factors 6,7 , we noted markedly elevated expression of granulocyte colony-stimulating factor receptor (G-CSFR, encoded by csf3r) in the developing somite 8 . Furthermore, G-CSFR was transiently expressed in regenerating myocytes of adult injured skeletal muscle, and extrinsic G-CSF supported short-term muscle regeneration in cardiotoxin-induced skeletal muscle injury 9 and crush injury 10 .…”
mentioning
confidence: 99%
“…Recent studies have shown that both BMP-2 and FGF-2 play an important role in early heart development, especially in the induction of the mesoderm component at the time of the formation of the three embryonic germ layers (Shimoji et al, 2010;Yuasa et al, 2005). In the present experimental protocol, this stage may correspond to the first three days of embryoid body formation.…”
Section: Long-term Cultivation Of Mipscs In Serum-free Medium 721mentioning
confidence: 93%
“…In the present experimental protocol, this stage may correspond to the first three days of embryoid body formation. Other studies have reported cardiomyocyte differentiation in spheroid cultures with fetal bovine serum or various inhibitors and hormones (Shimoji et al, 2010;Yuasa et al, 2005;Fujiwara et al, 2011;Hao et al, 2008;Olson et al, 2003;Pandur et al, 2002). This is a novel protocol to successfully elicit in vitro cardiomyogenic differentiation of miPS cells under defined serum-free culture conditions using FGF-2 and BMP-2.…”
Section: Long-term Cultivation Of Mipscs In Serum-free Medium 721mentioning
confidence: 99%